SENTENCE FEATURE IN STUDENTS’ ACADEMIC WRITING (Case Study in Polytechnic of Tonggak Equator Pontianak) - Magpika Handayani (Journal of English Educational Study (JEES), 2019)
Abstract: Academic writing is one type of writing that should be mastered by students in Polytechnic of Tonggak Equator Pontianak. Academic writing is very important because it functions as a way to express an idea or another way of communication in doing research. Academic writing is essential to process in writing academic articles. Moreover, writing skills are an important part of communication. Academic writing is a specific ability of communication to put writers’ ideas on paper, to organize their knowledge, and then how to make sentences become a paragraph. This research is descriptive qualitative research. The writer collected the data by giving instructions to the students to write an academic article. The respondents are 60 students who are the representative of the students from class A to F in semester 5. This semester is chosen because they have academic writing subject. The result of the research shows that the most crucial problem in writing a sentence in academic context by students of Polytechnic Tonggak Equator Pontianak is in the sentence category. In this problem, students are not able to vary their sentences in their paragraphs that might cause the quality of their sentence is not proficient.Keyword: Sentence Feature, Academic Writing, Politeknik Tonggak Equator Students